The Relationship Between Peer Social Support and Academic Resilience of Young Adult Migrant Students in Jakarta - Putri, Wening Cahya; Nursanti, Ade (UPI Press, 2020)
The more severe academic and psychosocial problems make young adult migrant students tend to have academic resilience to avoid psychological distress which could adversely affect their academic performance. One of the factors that help students to become resilient is protective factors, namely social support from the closest environment. Being away from family and relatives makes peers become the most intimate environment for young adult migrant students. Another consideration is that undergraduate young adult migrant students are at the stage of development where peers have a crucial role at this stage development. Based on this phenomenon, the present study is aimed to find out whether there is a correlation between peers’ social support and academic resilience among young adult migrant students. Social support itself is divided into two main categories: assistance related and non-assistance related. Participants in this study were 101, 17-25-year-old migrant students with at least 6-month experience studying in Jakarta and living without their parents. The research used a quantitative non-experimental method, employing the questionnaire of Social Provisions Scale and Academic Resilience Scale. The results of the correlation test (Spearman test) indicated that there was a significantly positive relationship between peer social support (assistance related r 0.472 (p = 0.00 0.05) and non-assistance related r 0.569 (p = 0.00 0.05)) and academic resilience among young adult migrant students. This result shows that that the higher the social support provided by peers, the higher the academic resilience of young adult migrant students will be.